Karakteristik Reksa Dana Dan Kinerja Reksa Dana Saham Di Indonesia - Christiana Fara Dharmastuti; Bernadus Dwiprakasa (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
A mutual fund is one of the interesting alternative modes of investment models for investors that do not have much time, knowledge and expertise in calculating the risk and investment return. This study is aimed to understand the influence of the mutual fund's characteristics: the expense ratio, fund size, turnover ratio, and the mutual fund's age towards the mutual fund's performance in Indonesia. This study has been conducted using the Fixed Effect Model with the White cross-section as the coefficient covariance method at 34 active equity mutual funds that existed in Indonesia during the 2012-2013 period. The result of this study has indicated that the expense ratio and the multi fund's age have a significant negative towards the the equities mutual funds in Indonesia while the fund size and the turnover ratios have a significant positive influence on the equity mutual fund's performance in Indonesia.